The Use of Targeted Next Generation Sequencing to Explore Candidate Regulators of TGF-β1’s Impact on Kidney Cells - Wang, Bo; Ji, Guanyu; Naeem, Haroon; Wang, Junwen; Kantharidis, Phillip; Powell, David; Ricardo, Sharon D. (Frontiers in Physiology, 2018)
Aims/hypothesis: Transforming growth factor-beta (TGF-β1) plays an important regulatory role in the progression of chronic kidney failure. Further, damage to kidney glomerular mesangial cells is central to the progression of diabetic nephropathy. The aim of this study was to explore the genetic associations between mRNA, microRNA, and epigenetics in mesangial cells in response to TGF-β1. Methods: The regulatory effects of TGF-β1 on mesangial cells were investigated at different molecular levels by treating mesangial cells with TGF-β1 for 3 days followed by genome-wide miRNA, RNA, DNA methylation, and H3K27Me3 expression profiling using next generation sequencing (NGS). Results: Our results provide the first comprehensive, computationally integrated report of RNA-Seq, miRNA-Seq, and epigenomic analyses across all genetic variations, confirming the occurrence of DNA methylation and H3K27Me3 in response to TGF-β1. Our data also provide evidence of the association between epigenetic changes and the expression of genes closely related to TGF-β1 regulation. Conclusions: This study has advanced our current knowledge of mechanisms that contribute to the expression of TGF-β1-regulated genes involved in the pathogenesis of kidney disease. The molecular underpinnings of TGF- β1 stimulation of kidney cells was determined, thereby providing a robust platform for further target exploration.